Obesity as a Potential Predictor of Disease Severity in Young COVID‐19 Patients: A Retrospective Study. Issue 10 (2nd September 2020) - Deng, Ming; Qi, Yongjian; Deng, Liping; Wang, Huawei; Xu, Yancheng; Li, Zhen; Meng, Zhe; Tang, Jun; Dai, Zhe
Abstract : Objective: This study aims to explore the indicators for severity of coronavirus disease 2019 (COVID‐19) in young patients between the ages of 18 and 40 years. Methods: This retrospective cohort study included 65 consecutively admitted patients with COVID‐19 who were between 18 and 40 years old in Zhongnan Hospital of Wuhan University in Wuhan, China. Among them, 53 were moderate cases, and 12 were severe or critical cases. Epidemiological, clinical, and laboratory characteristics and treatment data were collected. A multivariate logistic regression analysis was implemented to explore risk factors. Results: The patients with severe/critical cases had obviously higher BMI (average 29.23 vs. 22.79 kg/m 2 ) and lower liver computed tomography value (average 50.00 vs. 65.00 mU) than the group of moderate cases. The patients with severe/critical cases had higher fasting glucose, alanine aminotransferase, aspartate aminotransferase, and creatinine compared with patients with moderate cases (all P  < 0.01). More severe/critical cases (58.33% vs. 1.92%) had positive urine protein levels. The severe/critical cases also experienced a significant process of serum albumin decline. Logistic regression analysis showed that male sex, high BMI (especially obesity), elevated fasting blood glucose, and urinary protein positivity were all risk factors for young patients with severe COVID‐19. Conclusions: Obesity is an important predictor of COVID‐19 severity in young patients. The main mechanism is related to damage of the liver and kidney.